2019
DOI: 10.1136/bmjopen-2019-031332
|View full text |Cite
|
Sign up to set email alerts
|

HOMESIDE: home-based family caregiver-delivered music and reading interventions for people living with dementia: protocol of a randomised controlled trial

Abstract: IntroductionPharmacological interventions to address behavioural and psychological symptoms of dementia (BPSD) can have undesirable side effects, therefore non-pharmacological approaches to managing symptoms may be preferable. Past studies show that music therapy can reduce BPSD, and other studies have explored how formal caregivers use music in their caring roles. However, no randomised study has examined the effects on BPSD of music interventions delivered by informal caregivers (CGs) in the home setting. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 50 publications
0
46
0
Order By: Relevance
“…Baker, Grocke, and Pachana (2012) trained PCs to use music-sharing experiences and showed that this was beneficial to the spousal relationship, to satisfaction with caregiving, as well as to the PCs’ well-being. Baker et al (2019) also recently launched a large international three-arm parallel-group randomized controlled trial to determine whether caregiver-delivered music interventions improve caregivers’ quality of life and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Baker, Grocke, and Pachana (2012) trained PCs to use music-sharing experiences and showed that this was beneficial to the spousal relationship, to satisfaction with caregiving, as well as to the PCs’ well-being. Baker et al (2019) also recently launched a large international three-arm parallel-group randomized controlled trial to determine whether caregiver-delivered music interventions improve caregivers’ quality of life and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Drawbacks and technical limitations during the online sessions, the lack of physical contact between music therapist and patients Dowson B et al [ 15 ] Community case study The study examined the latest practice in online music-making in response to COVID-19 restrictions for people with dementia and their supporters. Over 50 examples were identified Benefits: accessibility, digital safety and well-being of participants Challenges: digital accessibility for some older people, audio latency and sound quality Gaddy S et al [ 16 ] Cross-sectional study survey Participants: 1196 professional neuro music therapists 51-item survey including questions related to employment, service delivery, perception of hope, perception of stress during the COVID-19 pandemic Benefits : many music therapists experienced changes in their positions, including a decrease in client contact hours and an increase in using alternative services, such as telehealth Challenges: Moderate level of perceived stress for the pandemic but at the same time great hope to improve tele-MT also in the future Ahessy, Bill et al [ 17 ] Survey-based study Participants: 11 parents of children and adolescents with visual impairment who engaged in online music therapy during the COVID-19 pandemic Results: 95% of parents perceived the teleheath programme to be a positive experience for their child, 73% observed positive behaviours directly after the sessions, and 82% (9/11) indicated that the programme was a valuable family resource that supported bonding and interaction Bompard S et al [ 18 ] Case study Participants: 14 patients with various neurological disorders (infantile cerebral palsy, genetic syndromes, brain malformations) and their parents received a customized MT (Euterpe method), 3 times a day for 2 consecutive weeks during the COVID-19 pandemic Results: improvement in children’s sleep quality and a reduction of parental distress …”
Section: Neurological Music Therapy Services From In Person (Pre-covi...mentioning
confidence: 99%
“…Most research within these fields has been carried out in the context of institutional dementia care. However, a growing body of research addresses singing and music for persons with dementia and their relatives in a home care setting (Baker et al, 2019;Baker et al, 2012;Clair, 2002;Kulibert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The research literature concerning singing and music as a systematic resource for persons with dementia and their families outside the institutionalised healthcare setting has been scarce but promising (Baker et al, 2012;Clair, 2002Clair, , 2016Kulibert et al, 2019). This research field is increasing, also with major ongoing studies (Baker et al, 2019). 3 Mostly, such research implies indirect music therapy: Music therapists instruct relatives to carry out music programs regularly, with a premeditated, often individually adjusted, but still predetermined program.…”
Section: Introductionmentioning
confidence: 99%